A Review of Nursing Position Statements on Racism Following the Murder of George Floyd and Other Black Americans - Knopf, Amelia; Budhwani, Henna; Logie, Carmen H.; Oruche, Ukamaka; Wyatt, Erin; Draucker, Claire Burke (The Journal of the Association of Nurses in AIDS Care, 2021)
National outrage over the killings of George Floyd and other Black Americans in the United States prompted public outcry against police brutality and racism in law enforcement and drew national attention to systemic racism as a public health crisis. In response, during the summer of 2020 many health organizations issued position statements in response to the murders. This article examines such statements issued by 3 prominent nursing organizations and 18 schools of nursing. Thematic analysis revealed six themes in the statements of the professional organizations, and a content analysis revealed that the statements of the schools of nursing were generally aligned with these themes. Such position statements can provide a viable approach to the public commitment to anti-racist reforms, but it is unclear if such statements can promote meaningful and measurable change.